Mobile banking: Exploring determinants of its adoption - Chuleeporn Changchit (2018)
© 2017 Taylor & Francis. As accessibility of technology, availability of information, and ability to interact through the Internet increase and evolve, more people are gravitating toward increasing their use of the Internet. Although the number of Internet banking users has grown rapidly in recent years, not all customers are ready to accept mobile banking services. It remains a challenge for banks to explore how to attract more customers to adopt the use of banking services via a mobile channel. This study examines the factors that impact acceptance of the use of mobile banking. A total of 309 subjects participated in this study. Data were collected via a survey instrument. A multiple regression analysis was used to analyze the data. Findings suggest factors that banks should consider when implementing mobile banking services, thus allowing them to design services that meet the needs of their customers.